Seasonal dynamics of two spirurid nematodes (Nematoda: Rhabdochonidae) in Schizothorax richardsonii (Gray,1832) from five collection sites of district Chamba, Himachal Pradesh, India - Kumari, Suman (2023)
The present study deals with the survey of nematode parasites from district Chamba (H.P.) India, during three different seasons and summarizes the data of prevalence, intensity, density and index of infections of Rhabdochona (Rhabdochona) denudata (Dujardin, 1845) Railliet, 1916 and Rhabdochona (Filochona) hellichi turkestanica (Skrjabin, 1917) Moravec et al., 2010 in freshwater fish, Schizothorax richardsonii (Gray, 1832). Fish samples were collected from five collection sites of district Chamba i.e. locality I (Chamba), locality II (Sukrala), locality III (Rari), locality IV (Saho) and locality V (Kheri). During the present study a total of 293 (92 ♂ + 201 ♀) randomly selected fish hosts were examined, in which 163 fish were infected with two species of nematodes. Seasonal studies for both the species from random sized hosts, exhibited higher prevalence, intensity, density and index of infection in summer season and least during rainy season. Of the two species, R. (Filochona) hellichi turkestanica dominated in four localities, with higher value of intensity of infection, density and index of infection during the three seasons.